2015
DOI: 10.1111/lam.12379
|View full text |Cite
|
Sign up to set email alerts
|

Skatole remediation potential of Rhodopseudomonas palustris WKU-KDNS3 isolated from an animal waste lagoon

Abstract: Odour pollution is a serious environmental problem, particularly in the agriculture industry, and technologies based on chemical remediation are less effective and cost prohibitive. In this study, the newly isolated Rhodopseudomonas palustris strain WKU-KDNS3 causes biodegradation of 3-methylindole (skatole), which is one of the most offensive odorants present in wastewater lagoons. Aerobic degradation of this widely spread aromatic pollutant by Rhodopseudomonas strain is a significant finding that enhances th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…PUF1 was a Gram-negative, rod, vibrioid or peanut shaped cells. It reported that R. palustris formed rosette-like clusters in older cultures and reproduced as budding [16]. The cell division occurred by budding was also observed (Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…PUF1 was a Gram-negative, rod, vibrioid or peanut shaped cells. It reported that R. palustris formed rosette-like clusters in older cultures and reproduced as budding [16]. The cell division occurred by budding was also observed (Fig.…”
Section: Resultssupporting
confidence: 52%
“…As shown in Fig. 2, cell suspensions under an NH 4 -N concentration ≤1.0 g/L always involved the characteristic absorption peaks at 806 and 866 nm indicating the presence of pigment bacteriochlorophyll a [16], while PUF1s of an NH 4 -N concentration of 6.0 g/L lost all the designated peaks from bacteriochlorophylls and carotenoids over the whole experimental period. Noticeably, suffering a middle NH 4 -N concentration of 3.0 g/L PUF1s restored its pigment synthesis ability after a six-day acclimation period.…”
Section: Resultsmentioning
confidence: 83%
“…Gu et al [45] reported that a methanogenic bacterial consortia derived from marine sediment from Victoria Harbour transformed 3-methylindole to 3methyloxindole, whereas a sulfate-reducing consortium mineralized 3-methylindole completely via 3-methyloxindole and -methyl-2-aminobenzeneacetic acid (Figure 7(c)). Sharma et al [89] isolated a new 3-methylindole-degrading purple nonsulfur bacterium, Rhodopseudomonas palustris WKU-KDNS3, from a swine waste lagoon using an enrichment technique. This bacterium could remove >93% of the total 3-methylindole in the medium by 21 days.…”
Section: Bacterial Degradation Of Methylindolementioning
confidence: 99%
“…There is yet a paucity of quantitative data on their capacity toward semi-volatile organic species such as C 2 –C 5 VFAs, phenolic, and indolic compounds. In fact, the presence of excessive SVOC levels have been recognized as one of the major concerns in: natural gas treatment 25 26 27 28 , animal housing facilities 29 30 31 , and sewage treatment plants 32 33 . Nonetheless, information regarding their treatment approaches is scanty due to their complex physiochemical properties (relative to common VOCs).…”
mentioning
confidence: 99%